Unlocking Bioethanol Production Potential: A Computational Exploration of Agri-Food Waste Valorization in Circular Bioeconomy Using Metagenomic Mining and Process Prediction Tools - Radu Tamaian; Corina-Teodora Ciucure; Elisabeta-Irina Geană (Proceedings)
In the pursuit of a sustainable approach to agri-food waste valorization, this paper delves into the realm of computational techniques to enhance our understanding and harness the potential for bioethanol production in a circular bioeconomy [...]